B56δ-related protein phosphatase 2A dysfunction identified in patients with intellectual disability - Gunnar Houge; Dorien Haesen; Lisenka E.L.M. Vissers; Sarju Mehta; Michael J. Parker; Michael Wright; Julie Vogt; Shane McKee; John L. Tolmie; Nuno Cordeiro; Tjitske Kleefstra; Marjolein H. Willemsen; et al. (The Journal of Clinical Investigation, 2015)
Here we report inherited dysregulation of protein phosphatase activity as a cause of intellectual disability (ID). De novo missense mutations in 2 subunits of serine/threonine (Ser/Thr) protein phosphatase 2A (PP2A) were identified in 16 individuals with mild to severe ID, long-lasting hypotonia, epileptic susceptibility, frontal bossing, mild hypertelorism, and downslanting palpebral fissures. PP2A comprises catalytic (C), scaffolding (A), and regulatory (B) subunits that determine subcellular anchoring, substrate specificity, and physiological function. Ten patients had mutations within a highly conserved acidic loop of the PPP2R5D-encoded B56δ regulatory subunit, with the same E198K mutation present in 6 individuals. Five patients had mutations in the PPP2R1A-encoded scaffolding Aα subunit, with the same R182W mutation in 3 individuals. Some Aα cases presented with large ventricles, causing macrocephaly and hydrocephalus suspicion, and all cases exhibited partial or complete corpus callosum agenesis. Functional evaluation revealed that mutant A and B subunits were stable and uncoupled from phosphatase activity. Mutant B56δ was A and C binding–deficient, while mutant Aα subunits bound B56δ well but were unable to bind C or bound a catalytically impaired C, suggesting a dominant-negative effect where mutant subunits hinder dephosphorylation of B56δ-anchored substrates. Moreover, mutant subunit overexpression resulted in hyperphosphorylation of GSK3β, a B56δ-regulated substrate. This effect was in line with clinical observations, supporting a correlation between the ID degree and biochemical disturbance.